2020
DOI: 10.20982/tqmp.16.4.p315
|View full text |Cite
|
Sign up to set email alerts
|

A Tutorial on Testing the Equality of Standardized Regression Coefficients in Structural Equation Models using Wald Tests with lavaan

Abstract: Comparing the effects of two or more explanatory variables on a dependent variable in structural equation models, with either manifest or latent variables, may be hampered by the arbitrary metrics which are common in social sciences and psychology. A possible way to compare the effects is the comparison of standardized regression coefficients by means of the Wald test. In this tutorial, we show how the Wald test can be used to compare standardized regression coefficients. Moreover, we demonstrate how this can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…To compare the indirect effects by groups, we performed a multiple mediator model with multiple groups by gender, using the Wald test for testing the group difference in the indirect path effects (Ryu and Cheong, 2017 ; Klopp, 2019 ). In the group of women, the frequency of coping activities was significantly associated with the increase in negative emotional states among women; however, in men, no significant relationship was observed between coping activities and emotional states.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the indirect effects by groups, we performed a multiple mediator model with multiple groups by gender, using the Wald test for testing the group difference in the indirect path effects (Ryu and Cheong, 2017 ; Klopp, 2019 ). In the group of women, the frequency of coping activities was significantly associated with the increase in negative emotional states among women; however, in men, no significant relationship was observed between coping activities and emotional states.…”
Section: Resultsmentioning
confidence: 99%
“…We used a modified Wald test to compare the magnitude of standardized regression coefficients (Klopp, 2020). Wald’s test indicated that the effects of Phonemic Proficiency on Real Word and Pseudo Word factors were not equivalent for ages 8–11 W (1, 480) = 15.475, p < .001, 12–19 W (1, 720) = 18.991, p < .001, or 20–50 W (1, 152) = 5.04, p =.02.…”
Section: Resultsmentioning
confidence: 99%
“…We reported pertinent coefficients for this model in Table 4. We used a modified Wald test to compare the magnitude of effects on the endogenous variables in the model (Klopp, 2020). The language and the Phonemic Proficiency subtests demonstrated equivalent effects on the Decoding factor in the 4–7, W (1, 480) = 2.51, p = .113), 12–19, W (1, 720) = .284, p = .594 and 20–50 groups, W (1, 152) = 1.111, p = .292.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Todas las covariables fueron controladas en el análisis, y el ajuste global se evaluó siguiendo las recomendaciones de Ullman y Bentler (44), (χ² no significativo, Índice de Ajuste Comparativo (CFI) ⩾ 0.95, Índice de Tucker-Lewis (TLI) ⩾ 0.90, Raíz del Error Cuadrático Medio de Aproximación (RMSEA) ⩽ 0.06, y Raíz Cuadrada Media Residual Estandarizada (SRMR) ⩽ 0.08). Finalmente, se usó el Wald test (45) para comparar los efectos directos entre hombres y mujeres. Para todos los análisis se usó un alfa de 0.05.…”
Section: Plan De Análisisunclassified